Moderating Role of Demographics on the Influence of Information Quality, Video Quality and Technology Ease of Use on Online TV Subscription in Tanzania - Masele, Juma James (University of Dar es Salaam Library Journal, 2026)
Although internet-based broadcasting has led to the emergence of a significant number of online television (TV) channels that offer subscribers more choices, the market shares each online TV enjoys vary considerably, with a few receiving huge subscription numbers and others receiving very few. Although previous studies from abroad affirm that online TV subscription is influenced by information quality, ease of use of online TV technology, and video quality, recent studies carried out in developing countries, including Tanzania, have not captured this consensus. However, scholars contend that online subscription varies among people and depends on context and/or demographic characteristics, due to differences in values, motivations, and expectations. It was from this motivation that the moderating effect of demographic variables—age and gender—on information quality, video quality and technology ease of use on Online TV subscription was assessed. The questionnaire was answered by 241 Online TV subscribers from Dar es Salaam, Tanzania. SmartPLS-SEM analyses revealed a significant influence of information quality and technology ease of use on Online TV subscription. The influence of video quality was insignificant, unless moderated by age. The moderation effect was lower by 0.123 for ages between 30 and 40 years than for ages between 18 and 29 years, while it was insignificant for ages between 40 and 60 years. The moderating effect of gender was insignificant. While ensuring the quality of information and making technology easy to use are important, a subscription win among youngsters requires improving video quality.